Extensão popular e produção de conhecimento: o caso do PPGE/UFPB - Araújo, Renan Soares de (2021)
The present study investigates the production of knowledge in Popular Extension, based on the dissertations and theses elaborated in the scope of the Postgraduate Program in Education of the Federal University of Paraíba. In the last decades, the dimension of University Extension has commonly stood out as a space that allows the encounter between different subjects with different cultures and knowledge, being even marked as a locus that enables the construction of new knowledge, due to this relationship that is established between the university institution and the reality experienced by diverse groups and social sectors. In this context, it is worth mentioning a wide and diversified set of practices that guide its actions based on the theoreticalmethodological and ethical-political assumptions of the concept of Popular Education (composing what has currently been identified with the concept of Popular Extension), in the valorization of popular knowledge gains centrality in extension work, with dialogue as the founding principle and the emphasis on building knowledge in a shared way. In this scenario, the Federal University of Paraíba has significant relevance, occupying a place of national reference, which can be distinguished by its historical tradition of developing Popular Extension initiatives and due to the expressive and strategic role that Postgraduate Program in Education has played as a place privileged in structuring research and developing knowledge in the field of Popular Education. In view of the above, the present dissertation aims to critically analyze what has been addressed in academic productions on Popular Extension has been approached by the dissertations and theses elaborated in the context of the Postgraduate Program in Education. Methodologically, this is an investigation with a qualitative approach, which was carried out from the realization of a bibliographical research of the type “state of the art”. The method adopted was historical-dialectical materialism and the theoretical-epistemological framework that guided the analysis and discussion of the data produced, based on contributions from authors in the field of Popular Education. The results show that Popular Extension presents itself as a dynamic field, which has thematic, disciplinary, theoretical-methodological and epistemological variability, in which different theories, concepts, categories and theoretical references are mobilized and articulated. In addition to evidencing understandings of Popular Extension as social work, a place for building knowledge and mobilizing learning, as well as a university social movement. Furthermore, some findings indicate the necessary assimilation of Popular Extension as a sign that coordinates different possibilities of what to do as an extensionist. It is concluded that the productions on Popular Extension have relevant epistemological variability, in which we witness the use of different theoretical-methodological and epistemological foundations with an important contribution to the construction of knowledge, permeated by a participatory approach, a critical worldview and an implication of social commitment.